Maternal Risk Factors and Perinatal Outcome in Women with Abruptio Placenta - Lilan Abdlkhaliq Abas; Ariana Khalis Jawad (Advanced Medical Journal)
Background and objective: Abruptio placenta is a significant cause of antepartum hemorrhage associated with fetal and maternal morbidity and mortality. Our objective was to determine the maternal risk factors and subsequent fetal and maternal outcomes in women with abruption placenta.